Control interno y su incidencia en la gestión cobranzas de la junta de agua potable regional norte, cantón la Maná, año 2012 - Quevedo Ortega, Verónica Elizabeth (2015)
The Internal Control is a tool of administrative management support to optimize resources, avoid the misappropriation thereof and provide effective information, through the Internal Control evaluation seeks to determine the existence or not of the weak controls to improve and achieve the objectives of the entity. The implementation of the Internal Control in this research seeks to assess the extent of the Internal Control in managing collections of the Junta of Agua Potable Regional Norte of Canton La Maná, year 2012. This work develops with the collection and of the institutional and bibliographic information through the use of interviews and direct observation of the processes executed in the State. Evaluation of the Internal Control allowed to detect weak points and let recommendations as corrective measures which contribute to the correct direction of the Department and of the entity. In what refers to the risk of audit was obtained the following results: level of trust 69.17% moderate, therefore a risk level of the 30.83% found moderate; the measurement of risks; 25% inherent risk, risk of 10% therefore as a result detection was obtained a risk of audit of the 0.75%.